Molecular epidemiology of livestock-Associated methicillin-resistant staphylococcus aureus (LA-MRSA) - Mello, Priscila Luiza [UNESP]; Pinheiro, Luiza [UNESP]; de Almeida Martins, Lisiane; de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP] (My University, 2021)
Recognized as one of the main causes of human infections worldwide, Staphylococcus aureus is also considered a harmful pathogen for veterinary medicine. This microorganism produces a significant number of virulence factors and may acquire resistance to methicillin, giving rise to the so-called methicillin-resistant S. aureus (MRSA), which have been considered a health issue for decades. When colonizing hospitalized individuals, MRSA is the main microbial agent related to Hospital-Acquired infections (HA-MRSA), being associated to high rates of morbidity, mortality and medical expenses. The epidemiology of MRSA has changed since the emergence of the Community-Acquired MRSA (CA-MRSA), strains that cause infections in healthy individuals. In 2003, a third epidemiological form, the Livestock-Associated MRSA (LAMRSA), was described first in Netherlands, followed by other countries. The majority of the LA-MRSA isolates have shown to belong to the clonal complex CC398, despite other clonal complexes and spa types have been observed. Although related to animal infections, the LA-MRSA strains demonstrate potential to colonize and infect humans, being considered a threat in occupational health, especially for farmers and veterinarians. The zoonotic reservoir for such isolates is believed to be farm animals, mainly swine. The indiscriminate use of antimicrobials in livestock is considered a risk factor for the presence of MRSA; however, the level of hygiene and contact/trading of animals are also important for its dissemination. In 2005, the transmission of LA-MRSA to farmers and their family members in Europe raised the concerns regarding their introduction in the community and hospitals. From 2012 to 2014, four people with no relation to swine production died due to sepsis caused by MRSA CC398 in Denmark, a country that produces around 30 million of swine and is one of the largest exporters in the world. In the Netherlands, the presence of LA-MRSA has been widely investigated in healthy swine, calves, horses and birds, and being described in dairy cattle as cause of subclinical mastitis. Although the infections caused by LA-MRSA in humans may seem unusual, such reservoir may significantly contribute to the raised global dissemination of MRSA. This phenomenon is especially worrying in countries presenting low prevalence of MRSA, since these strains have unexpectedly emerged in Europe and North America. The objective of this chapter is to provide data for a better understanding of the epidemiology and microbial properties of LA-MRSA.